Nafkah Bagi Istri Nusyûz Menurut Ibnu Hazm - Ayi Ishak Sholih Muchtar; Entan Sutarso (Istinbath | Jurnal Penelitian Hukum Islam, 2021)
In Islam, marriage is a bond of promise that justifies each husband and wife. With the marriage, it causes the husband to have to provide for his wife in the form of a living, kiswah and a place to live. However, according to most scholars, the obligation to provide a living can sometimes be lost when a wife is nusyûz. However, the opinion of the majority of scholars is not in line with the opinion of Ibn Hazm which states that the husband is obliged to provide a living for his wife even though the wife is in a state of nusyûz. Ibn Hazm's opinion about the obligation to provide a living for the wife of Nusyûz is seen from the time the marriage contract was established, whether the husband invited him to live at home or not. Because as long as there is a husband and wife bond, during that time there is also the right to live without providing other conditions, and all of that is adjusted to the conditions and abilities of the husband.